Penerapan Sanksi Pidana Bagi Notaris Pelaku Penggelapan Pajak Jual Beli Tanah (Studi Kasus Putusan Nomor: 300/Pid.B/2015/PN.Dps.) - Henny Hartati (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
In the past decade, there have been several Notaries involved in legal cases. One of them is a case of abuse of trust, in the form of using the money payment of tax on the sale of land entrusted by the client to the Notary, as in the Decision of PN Denpasar Number: 300 / Pid.B / 2015 / PN.Dps. dated 04 August 2015, that the Notary is declared as the defendant a criminal act of embezzlement. This paper aims to analyze: (1) the authority of Notary to receive and pay the tax on the sale and purchase of land, namely PPh and BPHTB, to the state treasury; and (2) the criminal sanction against the Notary. The results of this paper conclude: first, that the authority of Notary in accepting and paying the tax on the sale and purchase of land, namely PPh and BPHTB, to the state treasury is not regulated in legislation. However, a Notary has the authority if the client authorizes him. Secondly, that the Notary who is involved in the crime of embezzlement of the tax on the sale and purchase of land has fulfilled the formulation of Article 372 of the Criminal Code, thus being sentenced to 6 months imprisonment. However, this criminal sanctions does not need to be served by the Defendant, unless within 10 months there is a Judge Decision that the defendant has committed a crime.